Haematopathology of mice in acute experimental edwardsiellosis - Singh, B R; Singh, K P (The Indian Journal of Animal Sciences, 2012)
In experimentally induced edwardsiellosis in mice pathogenesis study was conducted. Edwardsiella tarda infection in mice after inoculation of L50, dose intraperitoneally. caused increase in clotting time (20-25 min) and haemoconcentration. Total erythrocyte count and leucocyte count dropped down within first 12 hr of infection then rose steadly. Differential leucocyte count depicted specific pattern. Gross as well as histopathological lesions corresponding to acute vasculitis were observed apart from desquamative gastroenteritis. Focal mononuclear cell infiltration were evident in hepatic lobules, renal medulla, interalveolar septa and serosa-submucosa of glandular stomach and upper small intestine.